Hendrabuana dan Seni Lukis Kaligrafinya (Kajian Biografi dan Estetika) - Hendi Linggarjati (Institut Seni Indonesia Yogyakarta, 2015)
Hendra Buana and his calligraphy painting (biography studies and aesthetics). Arabic calligraphy of contemporary art in Indonesia was pioneered by A. D. Pirous, Amri Yahya, followed by below-generation artists such as Syaiful Adnan, Hendra Buana, and Yetmon Amier. Developments in Indonesian contemporary Arabic calligraphy began to look MTQ atmosphere since the holding of the event in the city of Semarang in 1979. This study examines the biography of Arabic calligraphy artist Hendra Buana and his art characteristics. Biography analyzed by using the theory of Vera L. Zolberg, while the characteristics of his works are analyzed through the theory of Edmund Burke Feldman. This qualitative research data obtained through observation, interviews, document study and literature review. This study concluded that in the process of art, especially in Arabic calligraphy is influenced by several factors, both from internal and external. The study also concluded that the visualization of Arabic calligraphy on a painting by Hendra Buana will be built to process the wealth of artistic and meaningful traditional Arabic calligraphy art in the visual language of contemporary art of Arabic calligraphy. This research can provide an idea of how an Arabic calligraphy artist could exists and productive in the world art scene in Indonesia. The results could be used as a reference for writing the biography of the artist and his art in the future.Keywords: Hendra Buana, painting, Arabic calligraphy, contemporary.